Representations of deviance and crime: A comparative sociological reading of the past and present - Bouzid, Hacina (The International tax journal, 2025)
This study aims to examine the phenomenon of deviance and crime from a comparative sociological perspective by tracing the transformations in their representations between the past and the present and how these transformations have been reflected in the structure of social consciousness and the practices of social control across different societies. The study draws on the analysis of three research models: the first from Algeria, which addressed the value-based and social transformations that reshaped the concept of crime within the local context; the second from a Western country, which explored the impact of modernity and technology on the emergence of new forms of crime; and the third from an Arab Eastern country, which focused on the religious and cultural dimensions that shape society's perception of the deviant. This reading relies on the sociological comparative method supported by historical analysis of social discourse on deviance, aiming to understand the evolution of crime representations from cultural, moral, and institutional perspectives. The findings reveal that the concept of deviance is no longer static but evolves in accordance with value, social, and technological transformations. The moral and religious dimensions in explaining deviant behaviour have declined in favour of modern psychological and social approaches.